A feasible, acceptable and effective way to teach health care workers in low- and middle-income countries a method to manage acutely ill obstetric women. Issue 1 (January 2015) - McCarthy, Rose; Byrne-Davis, Lucie; Hart, Jo; Yuill, Gordon; Slattery, Helen; Jackson, Matthew; Byrne, Gerard J.
Abstract: Maternal mortality is unacceptably high in Sub Saharan Africa, which accounts for 56% of all maternal deaths (WHO, 2012 ). Most maternal deaths are avoidable but with prompt recognition and timely intervention it is not inevitable that acute or critical maternal illness deteriorates to fatality (Firth and Ttendo, 2012 ). This paper discusses a project to provide multidisciplinary training in Maternal-Acute Illness Management (M-AIM) in a low resource setting in order to actively address the third delay to women accessing emergency obstetric care: prompt receipt of effective care on reaching a medical facility. Highlights: Maternal mortality is high in low and middle income countries (LMIC), particularly Sub-Saharan Africa. Training health care workers to manage acute maternal illness could reduce mortality. Maternal AIM is a one day training package, delivered in Africa but not previously formally evaluated. Mat-AIM is acceptable (positive evaluation) and effective (improved knowledge) in Ugandan attendees. Further work will focus on health professional practice change in LMIC following education.